The results of using endoprosthesis in reconstructive-plactic surgery of breast cancer - Винник, Юрий Алексеевич; Фомина, Светлана Александровна; Гринева, Анастасия Юрьевна (ScienceRise: Medical Science, 2016)
Aim of research: the study of the remote results of breast reconstruction using endoprosthesis simultaneously with the surgical stage of combined and complex treatment of patients with BC. Materials and methods. 32 patients with BC who underwent the complex and combined treatment in the period 2012–2015 on the base of MIHP “Kharkiv regional clinical oncologic center” were under observation. At this study the given group of patients underwent hypodermic mastectomy with NAC kept and using silicone endoprosthesis as breast reconstruction. The largest group included women at the social active age 30–49 years old (66,7 %). The mean age of patients was 39,3 years old. The number of patients at the age of 60–69 years old was significantly less – 6,2 % (2 patients) of cases. The menstrual function on the whole was kept in 21 (65,6 %) patients and was absent for up to 5 years in 7 (21,8 %) patients and for more than 5 years in 4 (12,6 %) patients with BC. Results of research. At analysis of the results of research was established that the studied variant of reconstructive-plastic operative intervention in combination with hypodermic mastectomy with NAC kept as the surgical stage of combined and complex treatment of patients with BC has no essential effect on its remote results. The indices of both general survivability and the one without relapse depended only on the prognostic factors commonly acknowledged for this disease. Conclusions 1. The reconstructive-plastic operative intervention using endoprostheses simultaneously with hypodermic mastectomy with NAC kept does not worsen the remote results of neither combined nor complex treatment of patients with BC. 2. On the base of research was established the absence of influence of breast reconstruction on the increase of local relapses and remote metastases: 9,4 % and 6,2 % respectively